Acoso laboral o mobbing y violencia de género. - Fuentes-Valdivieso, Rocío (Revista de Sanidad Militar)
The object of the present study is to explain the process of conformation of the labour pursuit against the women in the institutions and organizations. This way, it is about giving to know a type of violence that it sometimes arises in a subtle way but the psychological and physique impact is irreversible. The women register multiple experiences of different types of pursuit, as long as they are subject to diverse forms of gender oppression described historically and they live pursuit most often in the work that is not always necessarily sexual. Mobbing, whose translation of the English language to Spanish is not so specific, it makes allusion to a kind of group pursuit that it is subtle and that it is increased in intensity until leaving men and women physically and emotionally disabled. The methodology used in this study is qualitative.